Implementasi Pendidikan Karakter Anak Usia Dini di RA Sabilul Huda Desa Laban Menganti Gresik - Syaikhon , Muhammad (LPPPM STAI Darul Hikmah Bangkalan, 2019)
This research is the kind of research the field with the approach descriptive qualitative with the title the implementation of character education early childhood in RA Sabilul Huda Laban Menganti Gresik. This research aims to review the process of implementation of character education on early childhood in RA Sabilul Huda Laban Menganti Gresik and to know the supporting factors and the inhibitors. Technique of data collection is by observation, in-depth interviews, and documentation. Analysis of data is with three stages, the reduction of data , presentation of data, and withdrawal conclusions/ verification These research findings can be concluded that the implementation of character education early childhood in RA Sabilul Huda Laban Menganti Gresik is through three rounds of including planning, implementation, and evaluation. The planning in the process of the implementation of characters education is begun by inserting the character values into the school curriculum, annual program, semester program, Program of Learning Plan weekly/Rencana Program Pembelajaran Mingguan (RPPM), and Program of Learning Plan dayly Rencana Program Pembelajaran Harian (RPPH). The process of implementation of character education is integrated in learning activities , exemplary, and habit.While the scoring in the process of applying character education integrated in the assessment of learning and spontaneous assessment conducted by educator. In the process of the implementation of character education in RA Sabilul Huda there are factors that support and inhibit. The factors that support the implementation of the character education are the charge of character education in the school curriculum, the motivations of school for the quality of output, the infrastructure that supports for the implementation of character education is enough. While the factors that inhibits the implementation of the character education are different characteristic students, the different environmental of students, the funding of character education still charged fully to the school, the students readily not focus, and the monitoring of the center of curriculum is not enough.